Uso de nanopartículas metálicas na vacinologia: implicações para o desenvolvimento de vacinas contra doenças infecciosas - Marques Neto, Lázaro Moreira (2018)
The search for new adjuvants is the main goal in vaccinology. Along with this, understanding the impact of using nanoparticles as a delivery system and immunomodulator in vaccine systems directly impacts the development of new vaccines. In this work, we seek to study and elucidate the adjuvanticity of magnetic nanoparticles, as well as its immunogenicity and protection of the vaccine systems. Initially, a literature review was made seeking scientific bases that demonstrated the possibility of using metallic nanoparticles (MeNPs) as innate immune system stimulators. It was also sought to find elements in which metallic nanoparticles could aid in the generation Th1, Th17 and T CD8 type cellular response. From this review, it was verified that the magnetic nanoparticles, or with metallic ions, were able to stimulate the activation of costimulatory molecules (CD80, CD40 and CD86), to induce secretion of cytokines (IL-1, IL-6, IFN-γ and TNF-α) as well as the humoral immune response, but no work demonstrated whether these nanoparticles were able to induce cellular response. Consequently, in the second part of the study, tuberculosis was used as model to verify if a vaccine formulation with a magnetic nanoparticle of manganese ferrite combined with recombinant fusion protein would have the ability to induce a protective cellular immune response, without adding other adjuvants. The nanoparticle was coated with recombinant CMX fusion protein and BALB/c mice were vaccinated with this formulation, in protocol with three vaccinations with 21-day intervals. Subsequently, the vaccinated animals were infected with Mycobacterium tuberculosis (H37Rv) to evaluate the protection conferred by the vaccine. The results showed that the nanoparticle was able to generate cellular immune responses of Th1, Th17 and T CD8 types, depending on the route of inoculation (subcutaneous, intranasal and mixed). The most preeminent response was Tc1 which was recalled after infection was able to protect against the challenge with Mtb. In addition, there was no appearance of side effects or damage to organs of infected animals, demonstrating that the formulation is safe. Finally, the vaccine formulations with MeNPs, more specifically with manganese ferrite, demonstrate potential application in vaccinology, and may be applied in vaccine formulations to generate cellular immune response, but the route must be considered and in case of use other adjuvants it should consider the possible interaction of NP with the molecule and their ligand.